Borneo Studies in History, Society and Culture - King, Victor T.; Ibrahim, Zawawi; Hassan, Noor Hasharina (Springer Singapore : Imprint: Springer, 2017)
This edited book is the first major review of what has been achieved in Borneo Studies to date. Chapters in this book situate research on Borneo within the general disciplinary fields of the social sciences, with the weight of attention devoted to anthropological research and related fields such as development studies, gender studies, environmental studies, social policy studies and cultural studies. Some of the chapters in this book are extended versions of presentations at the Borneo Research Council's international conference hosted by Universiti Brunei Darussalam in June 2012 and a Borneo Studies workshop organised in Brunei in 2012. The volume examines some of the major debates and controversies in Borneo Studies, including those which have served to connect post-war research on Borneo to wider scholarship. It also assesses some of the more recent contributions and interests of locally based researchers in universities and other institutions in Borneo itself. The major strength of the book is the inclusion of a substantial amount of research undertaken by scholars working and teaching within the Southeast Asian region. In particular there is an examination of research materials published in the vernacular, notably the outpouring of work published in Indonesian by the Institut Dayakologi in Pontianak. In doing so, the book also addresses the urgent matters which have not received the attention they deserve, specifically subjects, themes and issues that have already been covered but require further contemplation, elaboration and research, and the scope for disciplinary and multidisciplinary collaboration in Borneo Studies. The book is a valuable resource and reference work for students and researchers interested in social science scholarship on Borneo, and for those with wider interests in Indonesia and Malaysia, and in the Southeast Asian region.
Keywords: Social sciences.; Culture -- Study and teaching.; Anthropology.; elektronické knihy; electronic books